2001
DOI: 10.1002/pola.1177
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of brominated poly(isobutylene‐co‐isoprene)

Abstract: The thermal stability of brominated isobutylene–isoprene rubber (BIIR) was investigated through studies of the elastomer and a model compound that accurately represented the reactive functionality within the polymer. An analysis of commercial BIIR and reaction products of brominated 2,2,4,8,8‐pentamethyl‐4‐nonene (BPMN) by NMR demonstrated that bromination of isobutylene–isoprene rubber by 1,3‐dibromo‐5,5‐dimethylhydantoin yielded a kinetically favored exomethylene substitution product, 3‐bromo‐6,6‐dimethyl‐2‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 11 publications
2
77
1
Order By: Relevance
“…Unlike the polymeric system, brominated 2,2,4,8,8‐pentamethyl‐4‐nonene (BPMN or 1 ) derivatives are amenable to chromatographic separation and unambiguous structural characterization by NMR and high‐resolution mass spectrometry (MS). Previous studies6, 7 of the halogenation chemistry and thermal stability of this model have shown that it behaves in a manner consistent with BIIR, and this work extends these comparisons to nucleophilic displacements of bromide by thiolate anions.…”
Section: Introductionsupporting
confidence: 72%
“…Unlike the polymeric system, brominated 2,2,4,8,8‐pentamethyl‐4‐nonene (BPMN or 1 ) derivatives are amenable to chromatographic separation and unambiguous structural characterization by NMR and high‐resolution mass spectrometry (MS). Previous studies6, 7 of the halogenation chemistry and thermal stability of this model have shown that it behaves in a manner consistent with BIIR, and this work extends these comparisons to nucleophilic displacements of bromide by thiolate anions.…”
Section: Introductionsupporting
confidence: 72%
“…The high loss modulus, extended fatigue life, and oxidative stability of butyl rubbers have made them favorite materials in mechanical damping applications. By investigating the thermal stability of brominated butyl rubber, Parent and coworkers 7,8 reported the fact that at elevated temperatures (at vulcanization temperatures), exomethylene isomers of bromobutyl rubber rearranged to the more thermodynamically stable bromomethyl isomers followed by dehydrobromination to provide a butyl rubber with a conjugated diene structure. 3,4 Even though the sulfur-cured system has often been accepted for the vulcanization of IIR, the sulfur-cured system exhibits poor vulcanizate properties and low curing compatibility with other diene-based elastomers, such as polybutadiene or styrene-butadiene rubber, mainly because of the low level of unsaturation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the resulting bromonium ion may react with H 2 O to form a bromohydrin group. Furthermore, the signals at 122.4 (C29) and 124.8 (C28) ppm were assigned to the tertiary carbons of the conjugated cis ‐1,4‐isoprene units generated by elimination reaction of bromine atoms (Figure ), based on Parent et al These results demonstrate that natural rubber is brominated with NBS in latex stage, according to mechanism shown in Figure . Consequently, it is proved that the bromine atom is introduced into the natural rubber at the allylic position of the cis ‐1,4‐isoprene units while the bromohydrin structure of BrDPNRlatex is formed since the reaction occurs in the water.…”
Section: Resultsmentioning
confidence: 89%